Skeletal Stem Cells—A Paradigm Shift in the Field of Craniofacial Bone Tissue Engineering - Tevlin, Ruth; Longaker, Michael T.; Wan, Derrick C. (Frontiers in Dental Medicine, 2020)
Defects of the craniofacial skeleton arise as a direct result of trauma, diseases, oncological resection, or congenital anomalies. Current treatment options are limited, highlighting the importance for developing new strategies to restore form, function, and aesthetics of missing or damaged bone in the face and the cranium. For optimal reconstruction, the goal is to replace “like with like”. With the inherent challenges of existing options, there is a clear need to develop alternative strategies to reconstruct the craniofacial skeleton. The success of mesenchymal stem cell-based approaches has been hampered by high heterogeneity of transplanted cell populations with inconsistent preclinical and clinical trial outcomes. Here, we discuss the novel characterization and isolation of mouse skeletal stem cell (SSC) populations and their response to injury, systemic disease, and how their re-activation in vivo can contribute to tissue regeneration. These studies led to the characterization of human SSCs which are able to self-renew, give rise to increasingly fate restricted progenitors, and differentiate into bone, cartilage, and bone marrow stroma, all on the clonal level in vivo without prior in vitro culture. SSCs hold great potential for implementation in craniofacial bone tissue engineering and regenerative medicine. As we begin to better understand the diversity and the nature of skeletal stem and progenitor cells, there is a tangible future whereby a subset of human adult SSCs can be readily purified from bone or activated in situ with broad potential applications in craniofacial tissue engineering.